DA'HOM House of Beauty / Hasrina Hassan... [et al.] - Hassan, Hasrina; Emang, Octavia; Sumping, Maria; Tamin, Diana layah; Hassan, Anwar Fikri (2011)
A business plan is any plan that works for the business to look ahead, allocated research, and focus on the key points and prepare the problems and the opportunities. A business plan also needs to include the start-up plan. Start-up plan including the summary, mission statement, key to success, market analysis and break even analysis. This kind of plan is good for deciding whether or not to proceed with the plan to test if there is a business worth pursuing but it is not enough to run a business with. Besides that business plan also the yardstick by which business owner measure success in meeting stated goals and objectives. We decided to have our company with DA’HOM. Our business is focusing on proving our customers with a good service of beautician and health care based on their needs and lifestyle. Our DA’HOM will make our customers dreams come true by providing them with our “five star” service by making them look beautiful and healthier ways of life so that they will never feel despaired with their own appearance and health. We open up our DA’HOM in Mukah Sarawak because based on our survey, there still no any company that provides service like DA’HOM. We think that we must fulfilled this opportunity to open up this type of business and must willing to take all the risk. People always want to buy good service for them but the problem will appear after they had bought everything because they will find out that all the services that they purchased are not suitable or needed to them without proper advice by the proper beautician consultant. Therefore, DA’HOM is here to fix this type of problems by giving the customer variety of choice, tips and advice by our own consultant. And we promise that they will be 100% satisfied with our services.